Prediction of potential drug targets and key inhibitors (ZINC67974679, ZINC67982856, and ZINC05668040) against Rickettsia felis using integrated computational approaches - Rahman, Sudais; Liu, Hsien; Shah, Mohibuallah; Almutairi, Mashal M.; Liaqat, Iram; Tanaka, Tetsuya; Chen, Chien-Chin; Alouffi, Abdulaziz; Ali, Abid (Frontiers in Veterinary Science, 2025)
Rickettsia felis, responsible for flea-borne spotted fever, is a rising zoonotic pathogen posing an increasing global threat due to its expanding geographical distribution. The rise in antibiotic-resistant strains of this pathogen underscores the urgent need for new therapeutic interventions. This study employed a comprehensive subtractive proteomics analysis of the R. felis proteome, aiming to identify essential, non-host homologous, and pathogen-specific proteins, which were subsequently evaluated as potential new drug targets. These findings offer valuable insights into the development of therapeutic strategies against rickettsiosis. The analysis revealed 343 proteins that are non-homologous to the host, including 108 essential proteins, 25 unique metabolic pathways, and 11 distinct proteins. Out of these, 10 proteins were druggable in which two associated with virulence, and one related to resistance (succinate dehydrogenase). Through a rigorous screening process and extensive literature review, succinate dehydrogenase emerged as a promising drug target. Protein interaction partners for succinate dehydrogenase were identified using the STRING database. To further assess the functionality of succinate dehydrogenase, structure-based studies were conducted. Approximately 18,000 ZINC compounds were screened, leading to the finding of six potential inhibitors: ZINC67847806, ZINC67982856, ZINC67974679, ZINC67895371, ZINC05668040, and ZINC05670149. Absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling confirmed that most compounds met the preferred pharmacokinetic properties, except for ZINC67895371 and ZINC67847806, which exhibited positive ames test results, and ZINC05670149, ZINC67895371, and ZINC67847806, showed hepatotoxicity. All compounds were found to be non-sensitizing to the skin. Based on these findings, further experimental validation of ZINC67974679, ZINC67982856, and ZINC05668040 is recommended.